Geotechnical Aspects of Pavement Engineering. - Bandara, Nishantha (Geotechnical engineering collection., 2018)
Familiarity with geotechnical aspects of pavement engineering is essential for any practicing pavement or geotechnical engineer. When designing pavements on an existing roadbed or along a new alignment, accurate characterization of the existing subgrade condition plays an important and difficult task. In most situations, traditional geotechnical exploration and testing methods have been used to characterize the existing subgrade conditions. However, with the introduction of new Mechanistic-Empirical (ME) pavement design methods, there is a need for improved and more appropriate methods to characterize the exiting subgrade materials in order to predict future pavement conditions with better accuracy. Hence this handbook will be quite useful for practicing pavement engineers in terms of selecting proper field testing methods, characterizing subgrade materials, selecting proper pavement design, and treatment methods for unusual field conditions, and thus for effective construction of pavement foundations in general. This book introduces field exploration and testing methods from low-cost alternatives to accurate and efficient start-of-the-art methods. Another important feature of this book is the inclusion of an entire chapter devoted to dealing with unusual field conditions encountered in practice at times. This particular chapter provides design details and treatment guidelines to address such difficulties. This book is a valuable resource for any practicing pavement engineer or a civil engineering student who wishes to pursue a career in highway design and construction.